The Role of π Bridges in High‐Efficiency DSCs Based on Unsymmetrical Squaraines. Issue 5 (18th December 2012) - Delcamp, Jared H.; Shi, Yanrong; Yum, Jun‐Ho; Sajoto, Tissa; Dell'Orto, Elisa; Barlow, Stephen; Nazeeruddin, Mohammad K.; Marder, Seth R.; Grätzel, Michael
Abstract A series of squaraine‐based sensitizers with various π bridges and anchors were prepared and examined in dye‐sensitized solar cells. The carboxylic anchor group was attached onto a squaraine dye through π bridges with and without an ethynyl spacer. DFT studies indicate that the LUMO is delocalized throughout the dyes, whilst the HOMO resides on the squaraine core. The dye that incorporates a 4, 4‐di‐n‐hexyl‐cyclopentadithiophene group that is directly attached onto the π bridge, JD10, exhibits the highest power conversion efficiency in a DSC; this result is attributed, in part, to the deaggregative properties that are associated with the gem‐di‐n‐hexyl substituents, which extend above and below the π‐conjugated dye plane. Dye JD10 demonstrates a power‐conversion efficiency of 7.3 % for liquid‐electrolyte dye‐sensitized solar cells and 7.9 % for cells that are co‐sensitized by another metal‐free dye, D35, which substantially exceed the performance of any previously tested squaraine sensitizer. A panchromatic incident‐photon‐to‐current‐conversion efficiency curve is realized for this dye with an excellent short‐circuit current of 18.0 mA cm−2. This current is higher than that seen for other squaraine dyes, partially owing to a high molar absorptivity of >5 000 M−1 cm−1 from 400 nm to the long‐wavelength onset of 724 nm for dye JD10.